Comparative evaluation of platelet-rich fibrin membrane and collagen membrane along with demineralized freeze-dried bone allograft in Grade II furcation defects: A randomized controlled study - Mehta, Dhruv Bipinchandra (J Indian Soc Periodontol, 2018)
BACKGROUND: The management of the furcation areas in multirooted teeth is often challenging due to difficulty in access. Platelet-rich fibrin (PRF), a second-generation platelet concentrate, has shown to accelerate the healing of soft and hard tissues. This study was designed to evaluate the efficacy of autologous PRF as a membrane in treatment of Grade II furcation defects in molars as compared to collagen membrane along with demineralized freeze-dried bone allograft in both the groups. MATERIALS AND METHODS: A split-mouth study was planned with 18 patients having 2 sites of Grade II furcation defects each. Random allocation of the defect site was done for the test and control group. Plaque index, probing depth (PD), relative vertical clinical attachment level (RVCAL), gingival marginal level, and radiographic bone levels were recorded at baseline, 3 months, and 6 months postoperatively. RESULTS: Both the groups showed statistically significant outcomes in intragroup comparison from baseline to 3 and 6 months. However, there was no statistical difference between PRF membrane and collagen membrane groups on intergroup comparison. CONCLUSION: There was a significant reduction of PD, improvement in RVCAL, and defect fill with autogenous PRF as membrane. This indicates its role as a regenerative material in treating furcation defects, which can be used as alternative to other expensive membranes.